Socio-ecological determinants of malaria transmission risk among population residing in an endemic area of southern province of Karnataka, India - J. Gopika; K. Eshwari; Akhilesh Kumar Pandey; Ranjitha S. Shetty (Elsevier, 2024)
Background: India accounts for 79% of global malaria burden. With progress towards malaria elimination, assessment of true disease burden and determinants of its transmission risk is critical. The present study aimed to estimate the burden of malaria and identify socioecological factors determining the disease prevalence. Methods: A community-based cross-sectional study was carried out among 839 households covering 2910 individuals residing in Udupi taluk. A representative sample from urban, rural tribal and migrant communities were recruited and a questionnaire was used to collect information on socio-demographic, housing & behavioral factors. Data was collected using Epi-info mobile application version 7.2.4 and analyzed using SPSS version 16.0. Results: Among the population covered a total of 15 participants had a history of malaria in the past. Advancing age (AOR = 3.60; 95% CI: 2.14-6.04), illiteracy (AOR = 2.28; 95% CI:1.35-3.85), (AOR = 1.96; 95% CI:1.24-3.11) and rural (AOR = 1.96; 95% CI:1.39-2.74), tribal (AOR = 2.38; 95% CI:1.49-3.79), migrant (AOR = 4.28; 95% CI:2.30-7.98) localities were found to be independent predictors of disease awareness. With respect to malaria prevention practices, households from middle (AOR = 0.73; 95% CI: 0.49-1.09) & low SES (AOR = 0.30; 95% CI: 0.19-0.46) and those from migrant localities (AOR = 0.66; 95% CI: 0.38-1.14) were less likely to have poor practices. Conclusion: Age, education, socioeconomic status, and locality were found to be significantly associated with knowledge and practice towards malaria prevention. Creating awareness regarding malaria and its prevention with enhanced community participation in control activities jointly with local authority is further emphasized.